2010
DOI: 10.3109/00365513.2010.506926
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of topical and systemic melatonin administration on delayed wound healing in rats that underwent pinealectomy

Abstract: In conclusion, in the present study it was shown that wound healing was prolonged in experimental animals deprived of melatonin through pinealectomy. Melatonin exerts positive effects on wound healing, whether it is administered topically or systemically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…As melatonin exerts numerous antioxidant actions, a suppression of melatonin by LAN should be expected to decrease antioxidative mechanisms inasmuch as they depend on physiological nocturnal melatonin levels [ 232 ]. This assumption would be in line with the repeatedly observed increases in lipid peroxidation and decreases in glutathione peroxidase and superoxide dismutase in pinealectomized animals (e.g., [ 233 , 234 , 235 , 236 ]). Such a direct reduction of protective capacity must be distinguished from perturbed rhythms in protective enzymes and mitochondrial activity, which are induced by phase-shifting light signals that occur in inappropriate circadian phases and represent another aspect of chronodisruption.…”
Section: Output Pathways: Melatoninsupporting
confidence: 70%
“…As melatonin exerts numerous antioxidant actions, a suppression of melatonin by LAN should be expected to decrease antioxidative mechanisms inasmuch as they depend on physiological nocturnal melatonin levels [ 232 ]. This assumption would be in line with the repeatedly observed increases in lipid peroxidation and decreases in glutathione peroxidase and superoxide dismutase in pinealectomized animals (e.g., [ 233 , 234 , 235 , 236 ]). Such a direct reduction of protective capacity must be distinguished from perturbed rhythms in protective enzymes and mitochondrial activity, which are induced by phase-shifting light signals that occur in inappropriate circadian phases and represent another aspect of chronodisruption.…”
Section: Output Pathways: Melatoninsupporting
confidence: 70%
“…It has been shown that as an antioxidant, melatonin is at least twice as effective as vitamin E and five times more effective than glutathione (4,20). A few studies have demonstrated melatonin's potential effect on flap viability (4,5,21). Gurlek et al (4,5) performed pinealectomies in rats to prevent circadian melatonin secretion, thus enabling the assessment of antioxidant effects of exogenous melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…Bulbuller et al (2005) observed that subcutaneous melatonin application decreased collagen synthesis and epithelium proliferation and indicated undesirable effects on incision and anastomotic wound healing in normal and pinealectomized rats. However, positive improvement in the wound healing process has been detected due to topically and systematically administered melatonin on chronic wound healing in rats with pinealectomy (Ozler et al, 2010) and also on pressure ulcer in rats (Sener et al, 2006).…”
Section: Discussionmentioning
confidence: 99%